1982
DOI: 10.1246/cl.1982.1003
|View full text |Cite
|
Sign up to set email alerts
|

Revised Method for Calculation of Group Electronegativities

Abstract: Since Wilmshurst’s method for calculation of group electronegativity has some defects, the revised method was proposed for counting the number of valence electrons (n*) on the central atom A in radical −AB, and group electronegativities of more than 150 substituents were reasonably calculated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
75
1

Year Published

1987
1987
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 178 publications
(80 citation statements)
references
References 12 publications
4
75
1
Order By: Relevance
“…As opposed to authors of the work [15] we have not found the correlation of the DE i -values with C-substituents electronegativity (v) [27] (the electronegativity for CO 2 Me group and F were taken from references [28] and [29], respectively) and with the population of the nitrogen lone pair (N LP ) ( Table 2). …”
Section: Effect Of C-substituents On Inversion Barrier and C@n Bond Lcontrasting
confidence: 81%
“…As opposed to authors of the work [15] we have not found the correlation of the DE i -values with C-substituents electronegativity (v) [27] (the electronegativity for CO 2 Me group and F were taken from references [28] and [29], respectively) and with the population of the nitrogen lone pair (N LP ) ( Table 2). …”
Section: Effect Of C-substituents On Inversion Barrier and C@n Bond Lcontrasting
confidence: 81%
“…This is consistent with the distinct electron-withdrawing effect of the iodosyl group as expected from calculated group electronegativities. 17 Methanolic solution of 1-iodosyl-4-nitro-benzene has no long-term stability. After it was allowed to stand for several hours at room temperature, the 1 H NMR signals of 1-iodo-4-nitro-benzene appeared and increased steadily (Figs 1, 2).…”
Section: Resultsmentioning
confidence: 99%
“…However, comprehensive studies need to be carried out to ascertain the safety of QCSs in experimental animal models. Inamoto and Masuda (1982). b Taken from Ref.…”
Section: Discussionmentioning
confidence: 99%